2012
DOI: 10.1007/s12275-012-2068-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activities of flavonoids isolated from the bark of Rhus verniciflua stokes against fish pathogenic viruses In Vitro

Abstract: An 80% methanolic extract of Rhus verniciflua Stokes bark showed significant anti-viral activity against fish pathogenic infectious hematopoietic necrosis virus (IHNV) and viral hemorrhagic septicemia virus (VHSV) in a cell-based assay measuring virus-induced cytopathic effect (CPE). Activity-guided fractionation and isolation for the 80% methanolic extract of R. verniciflua yielded the most active ethyl acetate fraction, and methyl gallate (1) and four flavonoids: fustin (2), fisetin (3), butin (4) and sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 36 publications
0
56
0
1
Order By: Relevance
“…Butin and sulfuretin are the flavonoids, which contain pyrocatechol structure, and they have potent antioxidant activity and anti-viral activity (Kang et al 2012). The research showed that butin and sulfuretin are competitive inhibitors, and are not be combined with the copper ions of tyrosinase.…”
Section: Tyrosinase Effects On the Uv Visible Spectrum Of Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Butin and sulfuretin are the flavonoids, which contain pyrocatechol structure, and they have potent antioxidant activity and anti-viral activity (Kang et al 2012). The research showed that butin and sulfuretin are competitive inhibitors, and are not be combined with the copper ions of tyrosinase.…”
Section: Tyrosinase Effects On the Uv Visible Spectrum Of Compoundsmentioning
confidence: 99%
“…The extracts of Rhus verniciflua stokes have pharmacological activity such as anti-tumor activity , antioxidant activity (Lim et al 2001), anti-microbial activity (Kim et al 2010), and immunoregulation function (Kang et al 2012). Butin (7,3',Fig.1a) and sulfuretin (3',4',Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids include a large number of compounds which have been proven to possess a broad spectrum of biochemical and pharmacological activities such as antioxidant (Floreset, Wu, Negrin, & Kennelly, 2015;Zielinski et al, 2014), antibacterial (Cushnie & Lamb, 2011), antiviral (S. Y. Kang, J. Y. Kang, & Oh, 2012), etc. Therefore, highly efficient methods of extracting and isolating total flavonoids for supplements or medicinal use attract world-wide interest and studies (Cherng, Chiag, & Chiang, 2008;Pourcel, Routaboul, Cheynier, Lepiniec, & Debeaujon, 2007;Joana Gil-Chávez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The polyphenolic components, which can be considered as derivatives of phenol, are known to have many physiological functions, and they are also sources of natural tyrosinase inhibitors. They are abundant in the ethyl acetate fractions of plant extracts (Rao et al 2008;Kang et al 2012). Polyphenolic constituents in the ethyl acetate fractions may contribute to the high anti-tyrosinase activity.…”
Section: Composition and The Inhibition Rate Of The Extractsmentioning
confidence: 99%
“…It also is a traditional medicinal wood; the leaf, flower, roots, bark, fruit, and raw lacquer can be used as a medicine, for coughs, to eliminate addiction, act as an insecticidal compound, and to combat tumours. Recently, it has been found that phenolic extracts of R. verniciflua Stokes bark act as marked antioxidants (Lim et al 2001), anti-microbials (Kim et al 2010), antitumour compounds (Lee et al 2004), and function in immunoregulation (Kang et al 2012). The primary bioactive compounds are polyphenols, such as fisetin, fusin, butein, and sulphuretin (Kim et al 2006a). bioresources.com Chen et al (2014).…”
Section: Introductionmentioning
confidence: 99%